HUMAN PERFECTION AND THE ONTOLOGY OF LOVE IN MAHDUMI AZAM'S RISOLAI BITTIKHIYA (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article provides a comprehensive philosophical analysis of the concepts of human perfection, the ontology of love, and the process of irshad (spiritual guidance and moral cultivation) as articulated in a classical Sufi treatise. Special attention is devoted to the symbolic imagery employed in the text—such as earth, seed, water, and fire—which are interpreted as philosophical models representing the dynamic stages of human spiritual development and inner transformation. These metaphors are examined not merely as literary devices, but as conceptual tools that reveal the ontological and ethical dimensions of Sufi anthropology. The findings of the study substantiate that the analyzed treatise constitutes a significant intellectual source within Eastern philosophy, integrating anthropological perspectives with axiological values and offering a holistic understanding of human spiritual and moral perfection.